There are several ways to solve a system of equations, one of them is the elimination method.
The statement that can represent Bea's first step is (a) multiply the top equation by 2, then add the equations together.
The system of equation is given as:
[tex]3x - y = 23[/tex]
[tex]x + 2y = 10[/tex]
To eliminate y, we start by multiplying the top equation by 2
[tex]3x - y = 23[/tex]
This gives
[tex]2(3x - y = 23)[/tex]
[tex]6x - 2y =46[/tex]
Add this equation to the bottom equation
[tex]6x + x - 2y + 2y =46 + 10[/tex]
[tex]7x =56[/tex]
Notice that the variable y has been eliminated.
Hence, the possible first step is statement (a)
Read more about system of equations at:
https://brainly.com/question/14323743